THE RELATIONSHIP BETWEEN OIL PALM FRUIT CONDITIONS AND THE COLOR STABILITY OF PALM OIL: HUBUNGAN KONDISI BUAH SAWIT TERHADAP STABILITAS WARNA MINYAK SAWIT - Rangkuti , Ika Ucha P.; Syukri , Muhammad; Lubis, Nurhida Yani; Elisabeth, Jenny (Institut Teknologi Sawit Indonesia (ITSI), 2025)
This study aimed to determine the effect of fruit maturity levels on the oxidative color stability of crude palm oil (CPO) during heating. Fruit conditions used were unripe, ripe, overripe, and bruised. Samples were heated at 100°C for 0, 6, 12, 18, and 24 hours. The peroxide value and color (Red-Yellow) were measured using Lovibond Tintometer. Results showed that the combination of ripe and overripe fruits had the highest stability in red and yellow colors, while mixtures involving bruised and unripe fruits showed significant degradation. Prolonged heating accelerated the degradation of carotenoid pigments. The study indicates that fruit maturity significantly affects the oxidative stability of palm oil color.